2022
DOI: 10.3390/jrfm15080346
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk Characteristics of the Cryptocurrency Market: A GARCH-EVT-Copula Approach

Abstract: The cryptocurrency market offers significant investment opportunities but also entails higher risks as compared to other asset classes. This article aims to analyse the financial risk characteristics of individual cryptocurrencies and of a broad cryptocurrency market portfolio. We construct a portfolio comprising the 20 largest cryptocurrencies, which cover 82.1% of the total cryptocurrency market. The returns are examined for extreme tail risks by the application of Extreme Value Theory. We utilise the GARCH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Our review of the literature, however, found evidence that: (1) Bitcoin can be a potent hedge against stock indices at low frequencies; (2) the number of new companies accepting cryptocurrencies as payment can forecast cryptocurrency volatility; (3) Bitcoin's price volatility exhibits a "anti-leverage effect" because good news has a greater impact on volatility than bad news; and (4) bidirectional volatility spillovers in the cryptocurrency market, indicating market volatility in both directions. Our results are consistent with previous cryptocurrency reviews and add to them (Bowala, 2022;Bruhn, 2022;Guesmi, 2019;Klein, 2018;Wang, 2022;Yousaf, 2022a) To the best of our knowledge, there isn't a lot of research that addresses the volatility of cryptocurrencies, particularly using bibliometric analysis, as in our work, and compiling the numerous methods used to predict cryptocurrency volatility in a systematic way.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our review of the literature, however, found evidence that: (1) Bitcoin can be a potent hedge against stock indices at low frequencies; (2) the number of new companies accepting cryptocurrencies as payment can forecast cryptocurrency volatility; (3) Bitcoin's price volatility exhibits a "anti-leverage effect" because good news has a greater impact on volatility than bad news; and (4) bidirectional volatility spillovers in the cryptocurrency market, indicating market volatility in both directions. Our results are consistent with previous cryptocurrency reviews and add to them (Bowala, 2022;Bruhn, 2022;Guesmi, 2019;Klein, 2018;Wang, 2022;Yousaf, 2022a) To the best of our knowledge, there isn't a lot of research that addresses the volatility of cryptocurrencies, particularly using bibliometric analysis, as in our work, and compiling the numerous methods used to predict cryptocurrency volatility in a systematic way.…”
Section: Discussionsupporting
confidence: 91%
“…Options may be a vital tool for Bitcoin investors, providing important information, according to the available research (Bruhn, 2022). Results show that with a change of one percentage point in implied volatility, the premium appears to become more sensitive, whereas for a change of one percentage point in the risk-free rate across different expiration dates, the premium often stays the same.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…In this paper, we follow Börner (2020a, 2021) and use a fully automatic process to adapt a GPD that does not require any user intervention or additional parameters. This method was recently used successfully to determine tail risks in cryptocurrencies and showed advantages over other methods (Bruhn and Ernst 2022). In what follows, we use the same algorithm to determine the parameters of the GPD as the tail distribution.…”
Section: Generalized Pareto Distributionmentioning
confidence: 99%
“…Only when comparing the periods t 1 to TV is there a smoothing of the graphs compared to the graphs of the raw quantile. If the loss values above the specified confidence level are weighted with the various tail distributions and integrated, the values for the expected shortfall and thus for the mean CVaR are calculated; see (Embrechts et al 1997;McNeil et al 2015;Börner 2020b, 2021;Bruhn and Ernst 2022). Table 7 shows the results of the mean CVaR per period in comparison.…”
Section: Model and Datamentioning
confidence: 99%
“…The risks mentioned influence the expected value of a company's cash flows, the risk-adequate discount rate, as well as the need for equity capital to cover risks in a real imperfect market. The economic risks triggered by the severe economic crises have a low probability of occurrence but a high impact on a large number of companies (for the application of extreme value theory, see Bruhn and Ernst 2022). They are thus systematic risks.…”
Section: Changes In the Economic Fundamentals Due To Global Crisesmentioning
confidence: 99%